A community of singers: employing exploratory cluster analysis to reveal profiles of psychosocial characteristics among members of a street choir for homeless and formerly homeless individuals. Issue 1 (2nd January 2018) - Cronley, Courtney; Nordberg, Anne; Murphy, Erin Roark; Twis, Mary K.
ABSTRACT: This exploratory study employed cluster analysis to identify profiles of resilience, social support, stress, and mental health among members of a homeless and formerly homeless street choir; we examined the association between choir attendance and cluster membership, and the interaction of cluster membership and race. Respondents ( N  = 111, 66% African American, 84% homeless) had participated in the choir for an average of 12 months ( SD  = 12.02). We stratified the analysis according to homelessness status. Among those housed, k -means cluster analysis revealed two profiles: (1) relatively resourced but lower resilience, and (2) high resilience . Three profiles emerged among the homeless: (1) psychologically vulnerable, high stress and mental health concerns; (2) relatively resourced, showing average levels of mental health concerns and social support, minimally elevated stress, and higher resilience; and (3) low resilience . Examining the interaction, non-African American, housed participants in the high resilience cluster reported the most frequent choir attendance ( M  = 4.00, SD  = 0.00); among the homeless, non-African Americans in the psychologically vulnerable cluster reported the most frequent attendance ( M  = 3.88, SD  = 1.25). Results support the need for programs that address higher order needs concurrently with housing; they also highlight the ongoing need to provide particular outreach to minority populations.